MicroRNA Biophysically Modulates Cardiac Action Potential by Direct Binding to Ion Channel. Issue 16 (16th February 2021) - Yang, Dandan; Wan, Xiaoping; Dennis, Adrienne T.; Bektik, Emre; Wang, Zhihua; Costa, Mauricio G.S.; Fagnen, Charline; Vénien-Bryan, Catherine; Xu, Xianyao; Gratz, Daniel H.; Hund, Thomas J.; Mohler, Peter J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: MicroRNAs (miRs) play critical roles in regulation of numerous biological events, including cardiac electrophysiology and arrhythmia, through a canonical RNA interference mechanism. It remains unknown whether endogenous miRs modulate physiologic homeostasis of the heart through noncanonical mechanisms. Methods: We focused on the predominant miR of the heart (miR1) and investigated whether miR1 could physically bind with ion channels in cardiomyocytes by electrophoretic mobility shift assay, in situ proximity ligation assay, RNA pull down, and RNA immunoprecipitation assays. The functional modulations of cellular electrophysiology were evaluated by inside-out and whole-cell patch clamp. Mutagenesis of miR1 and the ion channel was used to understand the underlying mechanism. The effect on the heart ex vivo was demonstrated through investigating arrhythmia-associated human single nucleotide polymorphisms with miR1-deficient mice. Results: We found that endogenous miR1 could physically bind with cardiac membrane proteins, including an inward-rectifier potassium channel Kir2.1. The miR1–Kir2.1 physical interaction was observed in mouse, guinea pig, canine, and human cardiomyocytes. miR1 quickly and significantly suppressed IK1 at sub–pmol/L concentration, which is close to endogenous miR expression level. Acute presence of miR1 depolarized resting membrane potential and prolonged final repolarization of the action potential in cardiomyocytes. We identified 3 miR1-binding residues on the C-terminus of Kir2.1. Mechanistically, miR1 binds to the pore-facing G-loop of Kir2.1 through the core sequence AAGAAG, which is outside its RNA interference seed region. This biophysical modulation is involved in the dysregulation of gain-of-function Kir2.1–M301K mutation in short QT or atrial fibrillation. We found that an arrhythmia-associated human single nucleotide polymorphism of miR1 (hSNP14A/G) specifically disrupts the biophysical modulation while retaining the RNA interference function. It is remarkable that miR1 but not hSNP14A/G relieved the hyperpolarized resting membrane potential in miR1-deficient cardiomyocytes, improved the conduction velocity, and eliminated the high inducibility of arrhythmia in miR1-deficient hearts ex vivo. Conclusions: Our study reveals a novel evolutionarily conserved biophysical action of endogenous miRs in modulating cardiac electrophysiology. Our discovery of miRs' biophysical modulation provides a more comprehensive understanding of ion channel dysregulation and may provide new insights into the pathogenesis of cardiac arrhythmias.